Association Between Mental Health and Feeding Methods among 1- Month Postpartum Women in Japan: A Cross-Sectional Study - Masayo Matsuzaki; Hiroko Matsumoto; Mie Shiraishi; Risa Kobayashi; Sachi Watanabe; Megumi Haruna (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: The rate of predominant breastfeeding was 51.3% at 1 month postpartum, even though 93.4% of Japanese mothers expressed a desire to predominantly breastfeed during pregnancy. A wide range of historical, socioeconomic, cultural, and individual factors, as well as mental health, affect breastfeeding practices. However, the relationship between breastfeeding and mental health-depressive symptoms-has been controversial. Purpose: The aim of this study was to identify factors relationship including mental health and the feeding methods adopted by mothers at 1 month postpartum in Japan. Methods: A cross-sectional study was conducted at 2 Tokyo area hospitals between July and October 2014. We recruited a total of 560 eligible women. The participants included 392 women without severe illnesses or low birth weight babies at 1 month postpartum. The feeding methods were "mainly breastfeeding" (exclusively or mostly breastfeeding) and "mixed feeding and formula only". Depressive symptoms as a mental health were assessed using the Edinburgh Postnatal Depression Scale (EPDS). Multiple logistic regression analysis clarified the factors associated with mainly breastfeeding. Results: The mean (SD) age for the categories of mainly breastfeeding and mixed feeding and formula only was 33.0 (5.1) and 33.9 (5.5) years, respectively (p = 0.085). Women who were mainly breastfeeding at 1 month postpartum were more likely to be multiparous (adjusted odds ratio [AOR]: 1.80, CI:1.11 - 2.94), had EPDS score < 9 (AOR:1.87, CI:1.09 - 3.20), and had been desirous of breastfeeding from their pregnancy (AOR: 7.73, CI: 4.68 - 12.74). Conclusion: Our results suggested that healthcare providers should focus on the relationship between feeding methods and new mothers' mental health. Further research must identify effective care strategies for women who desire to breastfeed exclusively.